Developed-developing country partnerships: Benefits to developed countries? - Syed Shamsuzzoha B; Dadwal Viva; Rutter Paul; Storr Julie; Hightower Joyce D; Gooden Rachel; Carlet Jean; Nejad Sepideh; Kelley Edward T; Donaldson Liam; Pittet Didier (BMC, 2012)
Abstract Developing countries can generate effective solutions for today's global health challenges. This paper reviews relevant literature to construct the case for international cooperation, and in particular, developed-developing country partnerships. Standard database and web-based searches were conducted for publications in English between 1990 and 2010. Studies containing full or partial data relating to international cooperation between developed and developing countries were retained for further analysis. Of 227 articles retained through initial screening, 65 were included in the final analysis. The results were two-fold: some articles pointed to intangible benefits accrued by developed country partners, but the majority of information pointed to developing country innovations that can potentially inform health systems in developed countries. This information spanned all six WHO health system components. Ten key health areas where developed countries have the most to learn from the developing world were identified and include, rural health service delivery; skills substitution; decentralisation of management; creative problem-solving; education in communicable disease control; innovation in mobile phone use; low technology simulation training; local product manufacture; health financing; and social entrepreneurship. While there are no guarantees that innovations from developing country experiences can effectively transfer to developed countries, combined developed-developing country learning processes can potentially generate effective solutions for global health systems. However, the global pool of knowledge in this area is virgin and further work needs to be undertaken to advance understanding of health innovation diffusion. Even more urgently, a standardized method for reporting partnership benefits is needed-this is perhaps the single most immediate need in planning for, and realizing, the full potential of international cooperation between developed and developing countries.